Institutional designs and dynamics of crisis governance at the local level: European governments facing the polycrisis - Sabine Kuhlmann; Jochen Franzke; Niklas Peters; Benoît Paul Dumas (Policy Design and Practice)
This article analyses the institutional design variants of local crisis governance responses to the COVID-19 pandemic and their entanglement with other locally impactful crises from a cross-country comparative perspective (France, Germany, Poland, Sweden, and the UK/England). The pandemic offers an excellent empirical lens for scrutinizing the phenomenon of polycrises governance because it occurred while European countries were struggling with the impacts of several prior, ongoing, or newly arrived crises. Our major focus is on institutional design variants of crisis governance (dependent variable) and the influence of different administrative cultures on it (independent variable). Furthermore, we analyze the entanglement and interaction of institutional responses to other (previous or parallel) crises (polycrisis dynamics). Our findings reveal a huge variance of institutional designs, largely evoked by country-specific administrative cultures and profiles. The degree of de-/centralization and the intensity of coordination or decoupling across levels of government differs significantly by country. Simultaneously, all countries were affected by interrelated and entangled crises, resulting in various patterns of polycrisis dynamics. While policy failures and “fatal remedies” from previous crises have partially impaired the resilience and crisis preparedness of local governments, we have also found some learning effects from previous crises.